Degradation of Rhodamine B by Ultrasound/Fenton-Like Reagent - Zhang, Peng; Zhang, Wei; Zhang, Xue; Ren, Bozhi; Ma, Hongpu; Wang, Zhenghua (Asian Journal of Chemistry, 2014)
The catalytic oxidation of Rhodamine B using the ultrasound/Fenton-like process was investigated. 11.3 % of Rhodamine B using the ultrasound process and 50.1 % of Rhodamine B using Fenton-like process were obtained in 90 min. While the degradation of of Rhodamine B using ultrasound/Fenton-like process was 99.2 % obtained in 90 min. During the ultrasound/Fenton-like process, parameters affecting ultrasound degradation degree such as reaction time, pH, dosage of H2O2 and the dosage of Cr6+ were examined under the sound power was 250 W and the ultrasound frequency was fixed at 45 kHz. The results showed that after 90 min, the degradation degree could reach 98.1 % under the optimum conditions, when the initial pH value of the model dye was 3, the dosage of H2O2 was 11 uL and the dosage of Cr6+ was 0.8 mmol. In addition, the importance of the parameters on degradation degree was investigated by the model. The degradation degree was enhanced significantly as listed herein decreasing order of effectiveness: H2O2 dosage > Cr6+ dosage > Time > pH.